PERKEMBANGAN DEMOKRASI DI TUNISIA - Nurali, Rinawati Acan (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2021)
Abstract: This paper discusses the development of democracy in Tunisia. The goal is to understand the development of Tunisian democracy which is full of dynamics of the effects of the Arab Spring. This research uses the library method. Data collection through journals and books. The results of this study found that the long journey of the Tunisian people, in achieving independence from the occupation of the Tunisian government itself, was a road that was not easy, steep and sharp. Many became victims, in the name of the revolution. Both physically and psychologically. However, the struggle is carried out not only in the name of religion but also human humanity at stake, the rights and obligations desired by the Tunisian people, who become their driving force in their journey to achieve a democratic government. Of course, this requires a sacrifice in the long journey of democracy in Tunisia. Although in some Middle Eastern countries the process of democratization is still uncertain, Tunisia is not. Tunisia has become a hope for countries in the Middle East to rise from adversity. Tunisia has successfully held elections to democratically appoint a leader. Tunisian democracy is getting better with the inauguration of a new constitution that provides equality between men and women so that Tunisia becomes a pioneer of feminism in the Middle East. Although we cannot compare it with other contexts of Islamic government, Tunisia is a system that continues to rise to renew the slump of democracy by removing the influence of secular, far-right ideologies, and the monarchical system. Therefore, the political dynamics of the state system is a transition period whether it will lead to destruction or even towards democratic maturity, thus there is still optimism for the implementation of Islamic democracy in the Tunisian government system in the midst of all the dynamics that are faced.Abstrak: Tulisan ini membahas perkembangan demokrasi di Tunisia. Tujuannya untuk memahami perkembangan demokrasi Tunisia yang sarat dengan dinamika dampak Arab Spring. Penelitian ini menggunakan metode kepustakaan. Pengumpulan data melalui jurnal dan buku. Hasil penelitian ini menemukan bahwa perjalanan panjang rakyat Tunisia dalam mencapai kemerdekaan dari penjajahan pemerintah Tunisia sendiri merupakan jalan yang tidak mudah, terjal dan tajam. Banyak yang menjadi korban, atas nama revolusi. Baik secara fisik maupun psikis. Namun, perjuangan tersebut dilakukan tidak hanya atas nama agama tetapi juga kemanusiaan manusia yang dipertaruhkan, hak dan kewajiban yang diinginkan oleh rakyat Tunisia, yang menjadi pendorong mereka dalam perjalanan mencapai pemerintahan yang demokratis. Tentu saja, ini membutuhkan pengorbanan dalam perjalanan panjang demokrasi di Tunisia. Meski di beberapa negara Timur Tengah proses demokratisasi masih belum pasti, Tunisia tidak demikian. Tunisia menjadi harapan bagi negara-negara di Timur Tengah untuk bangkit dari keterpurukan. Tunisia telah berhasil mengadakan pemilu untuk menunjuk seorang pemimpin secara demokratis. Demokrasi Tunisia semakin baik dengan diresmikannya konstitusi baru yang memberikan kesetaraan antara laki-laki dan perempuan sehingga Tunisia menjadi pelopor feminisme di Timur Tengah. Meski tidak bisa kita bandingkan dengan konteks pemerintahan Islam lainnya, Tunisia adalah sistem yang terus bangkit untuk memperbaharui keterpurukan demokrasi dengan menghilangkan pengaruh ideologi sekuler, sayap kanan, dan sistem monarki. Oleh karena itu, dinamika politik sistem negara merupakan masa transisi apakah akan menuju kehancuran atau bahkan menuju kedewasaan demokrasi, sehingga masih ada optimisme penerapan demokrasi Islam dalam sistem pemerintahan Tunisia di tengah segala dinamika yang ada. dihadapi.